1995
DOI: 10.1172/jci118302
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus induces interleukin-10 by human alveolar macrophages. Suppression of early cytokine production and implications for incomplete immunity.

Abstract: IntroductionRespiratory syncytial virus (RSV) causes repeated infections thought to be due to an ineffective immune response. We examined the hypothesis that incomplete immunity may result, in part, from RSV-infected alveolar macrophage production of IL-10 which can interfere with the production of immunoregulatory cytokines. We also assessed whether RSV induced the expression of the 2',5' oligoadenylate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(71 citation statements)
references
References 44 publications
3
67
0
1
Order By: Relevance
“…The A2 strain has been shown either not to express IL-13 and mucus or to down-regulate those responses 11,13 while generating significant levels of IL-10 and interferon-␥. [35][36][37] Previous studies have examined the consequences of IL-10 depletion in knockout animals and in animals overexpressing IL-10 but not neutralization during infection in a normal animal during primary infection. 38,39 The overexpression of IL-13 in lungs of mice has been clearly linked to pathophysiological changes in not only allergic responses but in several other instances, including RSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The A2 strain has been shown either not to express IL-13 and mucus or to down-regulate those responses 11,13 while generating significant levels of IL-10 and interferon-␥. [35][36][37] Previous studies have examined the consequences of IL-10 depletion in knockout animals and in animals overexpressing IL-10 but not neutralization during infection in a normal animal during primary infection. 38,39 The overexpression of IL-13 in lungs of mice has been clearly linked to pathophysiological changes in not only allergic responses but in several other instances, including RSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Cells then were washed twice in MEM and subsequently covered in OptiMEM, 100 units͞ml penicillin, 100 g͞ml streptomycin, 50 mM Hepes (pH 7.5), 100 mM MgSO 4 , and 1.5% glycerol. After 5 h at 37ЊC, cells were scraped and sonicated as previously described (25). Aliquots of cell sonicates were flash-frozen in ethanol͞dry ice within 20 min of scraping.…”
Section: Methodsmentioning
confidence: 99%
“…When applied to HeLa cells, the 2-5A-antisense resulted in the ablation of PKR mRNA and enzymatic activity (24). The previous demonstration of elevated levels of RNase L after RSV infections of human alveolar macrophages (25) suggested that RSV might be susceptible to antiviral approaches involving RNase L. Here we show that the recruitment and activation of RNase L to an RSV mRNA with 2-5A-antisense oligonucleotides results in a potent inhibition of RSV replication in human tracheal epithelial cells.…”
mentioning
confidence: 94%
“…First, RSV-infected monocytederived myeloid DCs make very little IFN-␣/␤ relative to that made by HMPV-infected cells (56), and RSV blocks the induction of plasmacytoid DC maturation and IFN production in response to TLR7 and TLR9 agonists (134). Second, compared to influenza virus and HPIV3, RSV induces a somewhat different spectrum of cytokines from cord blood macrophages and DCs; specifically, there was a reduced level of IL-12 and a greater secretion of IL-10, IL-11, and prostaglandin E2, which might suppress T-cell activation and favor an increased Th2/ Th1 balance (7,114). Third, RSV infection of cord blood or monocyte-derived myeloid DCs decreased their capacity to activate CD4 ϩ T cells (7,29).…”
Section: Rsv Is Not Highly Cytopathic or Invasivementioning
confidence: 99%